The monks of the West: from St. Benedict to St. Bernard - Montalembert, Charles Forbes René de Tryon (W. Blackwood, 1861)
v. 1. Dedication. Introduction. book I. The Roman empire after the peace of the church. book II. Monastic precursors in the East. book III. Monastic precursors in the West. 1861. -- v. 2. book IV. St. Benedict. book V. St. Gregory the Great. Monastic Italy and Spain in the sixth and seventh centuries. book VI. The monks under the first Merovingians. book VII. St. Columbanus. The Irish in Gaul and the colonies of Luxeuil. 1861. -- v. 3. book VIII. Christian origin of the British isles. book IX. St. Columba, the apostle of Caledonia, 521-597. book X. St. Augustin of Canterbury and the Roman missionaries in England, 597-633. Appendix: Iona. Conclusions of the two papers of M. Varin. 1867. -- v. 4. book XI. The Celtic monks and the Anglo-Saxons. book XII. St Wilfrid establishes Roman unity and the Benedictine order, 634-709. book XIII. Contemporaries and successors of St. Wilfrid, 650-735. Appendix: Lindisfarne. Peterborough. Hexham. 1867. -- v. 5. Conclusion of book XIII. book XIV. Social and political influence of the monks among the Anglo-Saxons. book XV. the Anglo-Saxon nuns. 1867. -- v. 6. book XVIII. The church and the feudal system. The monastic orders and society. book XIX. St. Gregory, monk and pope. Appendix. 1879. -- v. 7. book XIX continued. book XX. The predecessors of Calixtus II. 1879.